Problems of innovation in the light of evolutionary theory - Vishnevsky, V.P.; Dementiev, V.V. (Економічний вісник Донбасу, 2010)
The article examines the features of the economic order that has been established in the former Soviet republics and impedes their innovative development. It is shown that this order, based on the family and clan private economic power, rejects the cooperation of economic actors that produce, select and inherit the “short rules” of interaction. It is proved that, in order to change it, it is necessary to create conditions for restricting the private economic power through co-opetition, the formation of organizational identification and “long rules” of interaction among the economic actors. Keywords: innovations, institutes, evolutional theory, economic order. У статті досліджено особливості господарського порядку, що склався в республіках колишнього СРСР і перешкоджає їх інноваційному розвитку. Показано, що цей порядок, заснований на сімейно-клановій приватній економічній владі, відторгає співпрацю економічних суб’єктів, що виробляють, відбирають і наслідують “короткі правила” взаємодії. Обґрунтовано, що для його зміни потрібно створити умови для обмеження приватної економічної влади за допомогою співпраці конкурентів, формування організаційної ідентифікації і “довгих правил” взаємодії економічних суб’єктів. Ключові слова: інновації, інститути, еволюційна теорія, господарський порядок. В статье исследованы особенности хозяйственного порядка, который сложился в республиках бывшего СССР и препятствует их инновационному развитию. Показано, что этот порядок, основанный на семейно-клановой частной экономической власти, отторгает сотрудничество экономических субъектов, которые вырабатывают, отбирают и наследуют “короткие правила” взаимодействия. Обосновано, что для его изменения требуется создать условия для ограничения частной экономической власти посредством сотрудничества конкурентов, формирования организационной идентификации и “длинных правил” взаимодействия экономических субъектов. Ключевые слова: инновации, институты, эволюционная теория, хозяйственный порядок.